2022
DOI: 10.1101/2022.10.19.512856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RND pumps across theAcinetobactergenus; AdeIJK is the ancestral efflux system

Abstract: Acinetobacter are generally soil-dwelling organisms that can also cause serious human infections. A. baumannii is one of the most common causative agents of Acinetobacter infections and is extensively drug resistant. However, an additional 25 species within the genus have also been associated with infection. A. baumannii encodes 6 RND efflux pumps, the most clinically relevant class of efflux pumps for antibiotic export, however the distribution and types of RND efflux pumps across the genus is currently unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
2
1
Order By: Relevance
“…Across the Gram-negative bacteria it is generally assumed that efflux pump sequences are conserved across a species, with genes present in common laboratory strains often taken as representatives of a whole species. This is despite several studies demonstrating that clinical isolates of Acinetobacter baumannii can lack adeB, which encodes the RND component of the AdeABC system associated with reduced antimicrobial susceptibility [32][33][34]. Here we show that while it is assumed that all E. coli isolates possess AcrB, AcrD, AcrF, CusA, MdtBC and MdtF, this is not true for the ST11 lineage.…”
Section: Discussioncontrasting
confidence: 83%
“…Across the Gram-negative bacteria it is generally assumed that efflux pump sequences are conserved across a species, with genes present in common laboratory strains often taken as representatives of a whole species. This is despite several studies demonstrating that clinical isolates of Acinetobacter baumannii can lack adeB, which encodes the RND component of the AdeABC system associated with reduced antimicrobial susceptibility [32][33][34]. Here we show that while it is assumed that all E. coli isolates possess AcrB, AcrD, AcrF, CusA, MdtBC and MdtF, this is not true for the ST11 lineage.…”
Section: Discussioncontrasting
confidence: 83%
“…The number of RND pumps present in different Gram-negative bacterial species varies and there is increasing evidence that prevalence of RND efflux pumps can also vary between isolates of the same species (Darby et al, 2023, Leus et al, 2020, Nowak et al, 2015, Nemec et al, 2007, Wieczorek et al, 2013). Yet it is still broadly assumed that all E. coli isolates possess six RND efflux pumps despite recent work…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of RND pumps can also vary within a genus. For example, we have recently shown that species across the Acinetobacter genus possess between two and nine RND pumps, with species most-commonly associated with human infection tending to encode more RND efflux pumps (Darby et al, 2023). A study by Ma et al found loss of MtrC function correlated with increased drug susceptibility in N. gonorrhoeae isolated from the cervical environment (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%